Design of an Arduino-based automatic sound timer system for mosques and prayer rooms - Fadlil, Fadlil; Tri Wahono; Edi Ismanto; Azaki Khoirudin (Journal of Natural Sciences and Mathematics Research, 2024)
The uncontrolled use of sound systems in mosques, especially after the call to prayer and iqomah, often leads to waste of energy and disturbances to the surrounding environment. This research aims to develop an Arduino-based automation system that can set the time of turning on and off the sound system in the mosque according to the adhan schedule, in order to improve operational efficiency and reduce electricity consumption. The system is designed using an Arduino UNO microcontroller, which regulates the sound device via a relay based on manually entered timing. Testing was carried out using Wokwi software simulations, and the results were then applied to a physical prototype. Testing is carried out with various time settings (5, 10, 15, and 20 minutes) to assess the accuracy and reliability of the system. The test results showed that the system was able to control the sound device with a 100% success rate in all the times tested. This system has proven to be effective in reducing the duration of unnecessary use of sound devices, potentially saving energy. The developed system provides a practical solution to reduce energy waste in mosques and improve the operational management of sound devices. Further implementation of this system in mosques can provide significant social and environmental benefits, especially in terms of congregational comfort and energy savings. Field testing as well as the development of IoT-based technologies in the future can expand the functionality of these systems.